2006
DOI: 10.1007/s00417-006-0341-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral epibulbar granulocytic sarcomas: a case of an 8-year-old girl with acute myeloid leukaemia

Abstract: Epibulbar granulocytic sarcoma in AML is rare (particularly in a child). We describe the first high-frequency ultrasound images and illustrate the use of a minimally invasive fine-needle aspiration biopsy technique to confirm our diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…[5][6][7] There is a tendency for it to develop in the orbits of children, arising from the adjacent orbital bones, whereas the cases which prove to be initial manifestations of pediatric AML are not uncommon. 7,8 Conjunctival 9-11 or eyelid involvement is even rarer, 12 an aleukemic case of which has only been reported once.…”
Section: Discussionmentioning
confidence: 94%
“…[5][6][7] There is a tendency for it to develop in the orbits of children, arising from the adjacent orbital bones, whereas the cases which prove to be initial manifestations of pediatric AML are not uncommon. 7,8 Conjunctival 9-11 or eyelid involvement is even rarer, 12 an aleukemic case of which has only been reported once.…”
Section: Discussionmentioning
confidence: 94%
“… 37 Even with appropriate treatment, conjunctival granulocytic sarcoma has been associated with a poor prognosis. 49 One case of bilateral subconjunctival hemorrhage in an infant as an initial AML manifestation has also been reported. 51 …”
Section: Methodsmentioning
confidence: 98%
“… 43 Studies have found that extramedullary involvement in general, and conjunctival leukemic infiltrates in particular, were more common in myelomonocytic and monocytic leukemia than other forms of AML. 49 Many authors suggested chemotherapy as the treatment of choice 50 while others advocate local radiotherapy. 37 Even with appropriate treatment, conjunctival granulocytic sarcoma has been associated with a poor prognosis.…”
Section: Methodsmentioning
confidence: 99%
“…This case is different from most other conjunctival myeloid sarcomas in that it arose in a chronic myeloproliferation rather than in an acute one. Another conjunctival example was reported in an 8-year-old girl with bilateral epibulbar myeloid sarcomas [10]. A unique presentation occurred in a 34-year-old apparently healthy woman who displayed involvement of the palpebral conjunctiva of all 4 eyelids with red, papular lesions [11].…”
Section: Discussionmentioning
confidence: 99%